E-GOVERNMENT IMPLEMENTATION THROUGH ‘SITANJAK MAKIN MANTAP’ APPLICATION BY SOCIAL OFFICE - Andriyus,; Rusadi, Sylvina; Monalisa, (Jurnal Governansi, 2023)
This study intends to describe the implementation of e-government through the Sitanjak Makin Mantap application by the Pekanbaru City Social Office This application is one way of bringing the concept of e-government into practice. E-government is innovation and creativity from the government in implementing all forms of policies to serve the public. However, in the implementation of applications, there are still many issues with application deployment, including a lack of funding for technology infrastructure and even a shortage of human resources. This study carried out observations and interviews in data collection Consequently, it may be stated that the study employed phenomenological-style qualitative research methodologies. The findings of the field study demonstrated that the Pekanbaru City social service's efforts to implement the application were still having difficulties due to ongoing funding and outreach issues, necessitating changes in the areas of support, quality, and value. For researchers who want to conduct research on the same topic, it is recommended to use theory-government.